Patient experiences of WALANT for outpatient upper limb surgery: A cross-sectional study of perioperative pain and anxiety - Reshlan Govender; Antoine G.L. Rocher; Mario T. Rankin; Khangelani Sondovana; Simphiwe C. Phenyane; Megan O'Connor (Journal of the Colleges of Medicine of South Africa)
Background: Demands on South African operating theatres have led to more outpatient upper limb surgery being performed under wide awake local anaesthesia no tourniquet (WALANT). This study aimed to determine patients’ anxiety and pain related to WALANT use in outpatient upper limb surgery, and to identify factors that increased the risk of heightened pain experiences.